THE EFFECT OF WORK DISCIPLINE AND WORK ABILITY ON THE QUALITY OF SERVICE IN THE DEPERTMENT OF PUPULATION AND CIVIL REGISTRATION OF TEGAL DISTRICT (CASE STUDY: MAKING E-KTP) - Lia Nur Amalia; Susi Sulandari; Dyah Hariani (Journal of Public Policy and Management Review, 2021)
ABSTRACT This research is intended to: (1) Know Work Discipline in Disdukcapil Tegal Regency; (2) Knowing Work Ability at Disdukcapil Tegal Regency; (3) Knowing the effect of Work Discipline on Service Quality in Disdukcapil Tegal Regency; (4) Knowing the effect of Work Ability on Service Quality in Disdukcapil Tegal Regency; (5) Knowing the effect of Work Discipline and Work Ability on Service Quality at Disdukcapil Tegal Regency. This method is quantitative. The population totaled 48,664. The sample in this study amounted to 100 respondents. The sampling technique used accidental sampling technique. Data analysis and hypothesis testing included validity, reliability, and determination coefficient tests. The data analysis technique used the Pearson product moment correlation coefficient. The results of this study indicate that: (1) the work discipline of the Tegal Regency Disdukcapil has an average of 2.93 in the Good category; (2) The work ability of the Disdukcapil of Tegal Regency has an average of 2.97 in the Good category; (3) Work Discipline has an effect on Service Quality in Disdukcapil Tegal Regency as indicated by the correlation results of 0.400> 0.05, with a contribution of 16%; (4) Work Ability affects Service Quality in Disdukcapil Tegal Regency which is indicated by the correlation result of 0.325> 0.05, with a contribution of 10.5%; (5) There is a positive and significant influence between the variables of work discipline and work ability on service quality with the results of 0.948> 0.05 at the 5% significance level. Based on the calculation of the coefficient of determination, the proportion of work discipline and work ability has an effect on service quality by 28.7% and the remaining 71.3% is influenced by factors not examined in this study.